2017
DOI: 10.1088/1674-1056/26/6/066101
|View full text |Cite
|
Sign up to set email alerts
|

Serrated magnetic properties in metallic glass by thermal cycle

Abstract: Fe-based metallic glasses (MGs) with excellent soft magnetic properties are applicable in a wide range of electronic industry. We show that the cryogenic thermal cycle has a sensitive effect on soft magnetic properties of Fe 78 Si 9 B 13 glassy ribbon. The values of magnetic induction (or magnetic flux density) 𝐵 and coercivity 𝐻 c show fluctuation with increasing number of thermal cycles. This phenomenon is explained as thermal-cycle-induced stochastically structural aging or rejuvenation which randomly flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Alternatively, aged glasses can be rejuvenated by recovery annealing above the glass transition temperature and then cooled down with a suitably fast rate [12][13][14][15][16]. The mechanical and magnetic properties can also be tuned by repeated thermal cycling at ambient pressure, which might result in rejuvenation or relaxation depending on the system size and thermal amplitude [17][18][19][20][21][22][23][24]. Nevertheless, the combined effect of periodic mechanical deformation and thermal cycling on the extent of relaxation and rejuvenation remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, aged glasses can be rejuvenated by recovery annealing above the glass transition temperature and then cooled down with a suitably fast rate [12][13][14][15][16]. The mechanical and magnetic properties can also be tuned by repeated thermal cycling at ambient pressure, which might result in rejuvenation or relaxation depending on the system size and thermal amplitude [17][18][19][20][21][22][23][24]. Nevertheless, the combined effect of periodic mechanical deformation and thermal cycling on the extent of relaxation and rejuvenation remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…From the correlation of magnetic properties and crystal structure changes during long-term low-temperature annealing, it has to be noticed that the first process of isothermal annealing at 210 and 260 °C is related with quenched-in stress relief that is related to a substantial initial increase of Bs with simultaneous decrease of P 10/50 and µ max . From the magnetic point of view, eliminating internal quenched-in stresses can improve the mobility of the Bloch wall of the magnetic domain 27 , and the magnetic anisotropy starts to fluctuate during the change of the topological short-range order 28 . From the point of view of the crystal structure, ageing in metastable quenched metallic glasses induces a lower enthalpy, a smaller volume, a more stable glassy state, and changes the topological short-range order, which is characteristic for the glass structure 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…From the point of view of the crystal structure, aging in metastable quenched metallic glasses induces a lower enthalpy, a smaller volume, a more stable glassy state and changes the topological short-range order, which is characteristic for the glass structure [23][24][25][26][27][28] Some of the previous studies have shown that the relaxation process of FeNiSiB systems can be divided into two stages: the first-metalloid atoms movement, the second-diffusion of the constituent atoms [29]. From the magnetic point of view, the elimination of internal stresses can improve the mobility of the Bloch wall of the magnetic domain [30] and, as a consequence, the magnetic anisotropy fluctuates during the change of the topological short-range order caused by the aging/rejuvenation process [31]. As the relative permeability is inversely proportional to the anisotropy constant, the magnetic saturation increases with the local structure change and the decrease in anisotropy constant [32].…”
Section: Resultsmentioning
confidence: 99%